25‐hydroxyvitamin D in malignant pleural disease: a prospective cohort study. (22nd August 2016) - Panagiotou, Marios; Papaioannou, Andriana I.; Kostikas, Konstantinos; Takou, Anna; Paraskeva, Maria; Kalkanis, Alexandros; Diamantea, Filia; Kastanakis, Emmanuil; Maropoulos, George; Filaditaki, Vasiliki; Karagianidis, Napoleon
Abstract: Introduction: Growing evidence suggests a role of vitamin D in various cancers but the significance of vitamin D in malignant pleural disease remains unexplored. We sought to investigate the concentration and diagnostic role of 25‐hydroxyvitamin D (25(OH)D) in malignant pleural effusions. Materials and Methods: Prospective study of consecutive treatment‐naïve patients with a new diagnosis of pleural effusion. Results: Seventy‐eight patients were studied, 45 of whom had malignant pleural effusions. Concentration of 25(OH)D in pleural fluid was significantly higher than serum in both malignant (15.2 ng/mL (9.7, 25.6) versus 10.2 ng/mL (6.4, 17.7), P < .001) and benign (11.4 ng/mL (8.4, 23.6) versus 7.9 (5.9, 16.1), P < .001) pleural disease. Pleural fluid 25(OH)D was almost significantly higher in exudates compared to transudates ( P = .050) but it did not differ significantly between malignant and benign effusions ( P = .217) and it was not diagnostic for malignant pleural disease (area under the ROC curve .58, 95% CI .45‐.71). Conclusions: In subjects with unselected pleural effusions, 25(OH)D in pleural fluid was not diagnostic for malignant pleural disease. The novel finding of convincingly and consistently higher 25(OH)D in pleural fluid than serum suggests a role for vitamin D in pleural disease and merits further research.